Car wash system software design using programmable logic controller and Qbasic language / Mohd Sayuti Ibrahim - Ibrahim, Mohd Sayuti (1995)
This thesis describes a general view of the software design of a car washing system which has the ability to improve the operation of the car wash system in Malaysia. The system uses a programmable logic controller (PLC) unit and a host link system as a communication module from PLC to computer. The PLC will control the system by controlling the input and output devices. Any information about the condition of the system, will be sent by PLC to the computer through the host link system. This information is presented through the graphics display unit as a supervisory facility in order to have an efficient operation. All the sequences of the process such as washing, drying and polishing will automatically be controlled by the PLC.